Blood-Glucose-Lowering Effect of Coptidis Rhizoma Extracts From Different Origins via Gut Microbiota Modulation in db/db Mice - Yuanfeng Lyu; Lin Lin; Yuning Xie; Dan Li; Min Xiao; Yufeng Zhang; Stanley Chun Kai Cheung; Pang Chui Shaw; Xiao Yang; Paul Kay Sheung Chan; Alice Pik Shan Kong; Zhong Zuo (Frontiers Media S.A., 2021)
Background:Coptidis rhizoma extracts (CREs) have been used widely for their anti-diabetic and anti-microbial activities, and berberine/jatrorrhizine/coptisine/palmatine are the primary bioactive components. Although guidelines have adopted content analyses of these components as a quality control method for CREs, it is difficult to differentiate the CREs from different sources using this method because of the lack of indications for their related pharmacological activities.Purpose: To explore the effect of CREs (CREA/CREB/CREC) with different compositions of major components on the gut microbiota and blood glucose levels in db/db mice.Methods: Degradation of berberine/jatrorrhizine/coptisine/palmatine from CREA/CREB/CREC in rat/mouse intestinal contents and their impact on nine common gastrointestinal bacteria were investigated. In addition, the effects of oral administration of CREA/CREB/CREC for 2 weeks on the gut microbiota and blood glucose levels in db/db mice were monitored via insulin/glucose tolerance test (ITT/GTT), insulin concentration, homeostatic model assessment of insulin resistance and fecal 16S rRNA sequencing.Results and Conclusion: The total amount of berberine/jatrorrhizine/coptisine/palmatine was highest in CREA. Clostridium perfringens was strongly inhibited by all three CREs, with CREA demonstrating the most significant inhibitory effects on minimum inhibitory concentration, time-kill kinetics, and ATP production. In db/db mice, CREA resulted in the most significant decrease in ITT/GTT and depicted different changes in the microbiota from CREB/CREC. Thus, CREs with different compositions of berberine/jatrorrhizine/coptisine/palmatine differed in terms of time-kill kinetics and ATP production assays on C. perfringens. CREA revealed the potent bacterial inhibitory effects and glucose-lowering activity.